Women’s Social Movements, Land Conflict, and Ecofeminism: A Study in Jambi Province, Indonesia - Muliono Muliono; Alya Triska Sutrisno; Mariatul Qibtiyah; Galank Pratama (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2025)
The continuation of land conflicts has ecological, economic, and social implications. This has motivated women survivors of conflict to organize movements. This study aims to explore the strategies, patterns, and forms of the movement and its meaning in relation to ecofeminism. This research uses qualitative methods. The results of the study show that, first, the women's movement is a reformative movement. Second, the movement's strategies involve protests and framing, mobilizing solidarity through religious activities, and environmental empowerment. These strategies affirm the value of ecofeminism in movements organized by local women. This study concludes that the movement of women survivors of land conflict reflects the ecofeminist movement, by voicing justice at the local level as well as an effort to deconstruct the legacy of agrarian colonialism, which is structurally unequal and gender biased. This study contributes to the study of ecofeminism in Indonesia by enriching the agrarian-based conceptual understanding and experiences of local women's movements.